Evaluation of Nursing School Educators' Knowledge and Attitudes Regarding Infant Sleep Safety. Issue 4 (July 2018) - Cirelli, Jane; Clymer, Beverly; Burgess, Adriane; Aguilar, Jennifer; Bell, Theodore; Goodstein, Michael
Abstract: AIM: The purpose of this study was to evaluate nursing educators' attitudes and knowledge regarding current American Academy of Pediatrics recommendations for a safe infant sleeping environment. METHOD: This was a cross-sectional prospective survey of all nursing programs with associate degrees or higher in the United States. Instructors teaching pediatric and obstetric didactic or clinical material at an Accreditation Commission for Education in Nursing-approved nursing school could participate. RESULTS: Of 396 educators surveyed, 70 percent identified all sudden infant death syndrome risk factors. Correct responses for individual safe sleep recommendations ranged from 99 percent for correct room temperature to 53 percent for pacifier use; 9 percent said it was safest for infants to sleep in a position other than on the back. CONCLUSION: Nursing educators need ongoing training on infant sleep safety to maintain mastery of the information that students need for competency in the workforce involving infant care. Abstract : Supplemental digital content is available in the text.